Efficient optogenetic silencing of neurotransmitter release with a mosquito rhodopsin - Mahn, Mathias; Saraf-Sinik, Inbar; Patil, Pritish; Pulin, Mauro; Bitton, Eyal; Karalis, Nikolaos; Bruentgens, Felicitas; Palgi, Shaked; Gat, Asaf; Dine, Julien; Wietek, Jonas; Davidi, Ido; et al. (Neuron, 2021)
Information is carried between brain regions through neurotransmitter release from axonal presynaptic terminals. Understanding the functional roles of defined neuronal projection pathways requires temporally precise manipulation of their activity. However, existing inhibitory optogenetic tools have low efficacy and off-target effects when applied to presynaptic terminals, while chemogenetic tools are difficult to control in space and time. Here, we show that a targeting-enhanced mosquito homolog of the vertebrate encephalopsin (eOPN3) can effectively suppress synaptic transmission through the Gi/o signaling pathway. Brief illumination of presynaptic terminals expressing eOPN3 triggers a lasting suppression of synaptic output that recovers spontaneously within minutes in vitro and in vivo. In freely moving mice, eOPN3-mediated suppression of dopaminergic nigrostriatal afferents induces a reversible ipsiversive rotational bias. We conclude that eOPN3 can be used to selectively suppress neurotransmitter release at presynaptic terminals with high spatiotemporal precision, opening new avenues for functional interrogation of long-range neuronal circuits in vivo.
CRIS-Team Scopus Importer:2021-11-16
Keywords: autaptic neurons; dopaminergic; eOPN3; G protein-coupled receptor; GCPR; inhibitory; mosquito; optogenetics; presynaptic; silencing; thalamocortical